ANALYSIS OF RASIOLEGIS OF HONORS AGAINST ETHICS ENFORCEMENT ADVOCATE PROFESSION - Dr Agus Pramono (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2018)
This paper aims to analyze the legal counselors' advocacy against the enforcement of advocate professional ethics. An advocate Honorary Board as aninstitution formed by a functioning Advocate Organization and authorized to oversee the implementation of the Advocate's code of ethics. This is so that every advocate as a profession holder remains in professional values, is responsible and upholds the profession he holds, considering that the Advocate's status as Law Enforcement is one of the instruments in the judicial process which has an equal position with other Law Enforcement. This study uses a normative juridical approach, and secondary data as the main data supported by primary data. The secondary data in the form of primary, secondary and tertiary legal materials are analyzed qualitatively. Based on the analysis revealed that in Law No. 13 of 2003 concerning Advocates, stated that Peradi was the sole forum for advocacy organizations but with the presence of KAI coupled with divisions in Peradi's body which finally issued a Circular Letter of the Supreme Court of the Republic of Indonesia No. 73 KMA / HK.01 / IX / 2015 the application or xecution of decisions against violations of the code of ethics by advocates is difficult to implement.